Linezolid resistance in multidrug-resistant mycobacterium tuberculosis: A systematic review and meta-analysis - Azimi, Taher; Khoshnood, Saeed; Asadi, Arezoo; Heidary, Mohsen; Mahmoudi, Hassan; Kaviar, Vahab Hassan; Hallajzadeh, Masoume; Nasiri, Mohammad Javad (Frontiers in Pharmacology, 2022)
Introduction: Tuberculosis (TB), resulting from infection by Mycobacterium tuberculosis (M. tuberculosis), is an important and resurgent global health problem. Linezolid is an effective antibiotic with which to treat patients failing drug-resistant TB treatment. In this study, we performed a systematic review and meta-analysis to investigate the prevalence of linezolid resistance among MDR-TB isolates, global. Method: Using the PRISMA guidelines, databases of, Embase, and PubMed and Web of Science were searched systematically from Janurary 2000 to April 2021. Statistical analyses were performed by using Comprehensive Meta-Analysis software. Heterogeneity reported by using the t2 and Q statistics. Egger’s weighted regression and Begg’s rank correlation in combination with funnel plot were used to evaluate any possible publication bias. Results: A total of 25 studies were included from 14 different countries, with the majority of the China (n=5), Turkey (n=4). Also, 7366 patients infected with MDR M. tuberculosis were enrolled in current study. Of the study population, 97 patients were co-infected with HIV and 18 patients with HCV. Furthermore, 28 patients had diabetes and139 patients were alcohol abuser. Overall, 4956 MDR M. tuberculosis strains were isolated from TB patients. The pooled frequency of linezolid resistance among clinical isolates of MDR M. tuberculosis was 4.2% (95%). Begg’s (p = 0.72) / Egger’s (p = 0.03) test, showed that there was some evidence of publication bias. Conclusion: Our study showed that the global linezolid resistance among MDR-TB is low and this antibiotic can be used as an anti-tuberculosis drug in treatment regimes.